ASSESSMENT OF NURSES MANAGEMENT SKILLS FOR CRITICALLY ILL PATIENTS - Ali, S; Gillani, SA; Afzal, M; Parveen, K (Biological and Clinical Sciences Research Journal, 2020)
The Nurses usually use physical restraints for maintaining patients’ therapies and devices in a critical ill setting like ICU, like central lines, endotracheal tubes and the arterial lines. It has been found that about up to 78% among the critical ill patients who have been admitted into various types of ICUs and may have a need for applying a physical self-possession due to the alterations found among their levels of the awareness while during their stay at ICU ward. The nurses' attitude, knowledge and their practice for physical self-control played a vital role for nursing care which has to be provided for restrained patients to prevent form complications in ICU. We have conducted our research to assess nurse's attitudes, knowledge and practice regarding their physical self-control among the most critically ill patients in ICU. We have used a descriptive type of design for our study. The number of nurses used for our study was 66 in total who are working at Lahore School of Nursing, The University of Lahore, Lahore, Pakistan. From our study most of the samples were female, who had a bachelor degree in nursing, with experience of more than 5 years, the aged was ranged between 21-30 years old, along with not attended any of the previous degree or equivalent educational program related with self-control or restraints were under consideration. It was found from our study that majority of samples under study were with reasonable level of nursing knowledge, offensive type of attitude however, around 90.8% out of all nurses showed a satisfactory and moderate type of practice for applications of the physical self-control or restraints for critical ill patients in ICU. It was frond from correlation among the socio-demograhpic characters and nurses` knowledge, the practice and attitude, no significant type of correlation was recorded while among the nurses' age vs knowledge, the practice and attitude, a significant and positive correlation was found while among the nurses’ knowledge, gander and practice was also found a significant correlation along with nurse’s practice and qualification, a significant positive correlation was also among the nurses’ practice score, attitude and experience. It was concluded from our study that, a reasonable level of nurses' improper attitude, knowledge and a satisfactory practice for physical self-control or restraints was found among the critically ill patients in ICU. From our study we have suggested that there must be some proper training programs to teach nurses to develop their knowledge and physical restraints while working in ICU for proper care of patients.